(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the behavior of undergraduate Law students, in relation to alcohol consumption and driving. Cross-sectional study with law students from a private educational institution in Aracaju/SE. To assess the socio-demographic and academic profile, and to verify the individuals who drink and drive, questions were elaborated based on the I National Survey on the use of Alcohol, Tobacco and other Drugs, complemented with the Youth Risk Behavior Survey (YRBS). The Alcohol Use Disorders Identification Test (AUDIT) was used to assess the pattern of alcohol consumption. Pearson’s chi-square, Pearson’s chi-square tests with Monte-Carlo simulation and Fisher’s exact test were used. Crude odds ratios were estimated for the variables that obtained p <0.2 in the univariate analysis and adjusted for the variables that together were significant at 5%. 358 students were evaluated, with an average age of 21.7 years, 51.4% female, 96.9% single. Of the students, 21.2% drove under the influence of alcohol in the last 12 months. The prevalence of students hitchhiking with a drunk driver was 33%. Only one academic was fined by the police for driving while intoxicated (0.3%). The risky drinking group has a 2.33-fold chance of driving under the influence of alcohol. It is concluded that although it is a population of higher education and knowledgeable about the legislation, there is a high prevalence of alcohol use associated with driving, which implies the need for improvements in the prevention and inspection campaigns of driving under the influence of alcohol.